2022
DOI: 10.3390/ani12192672
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sugar Beet Silage, High-Moisture Corn, and Corn Silage Feed Supplementation on the Performance of Dairy Cows with Restricted Daily Access to Pasture

Abstract: A study was undertaken to assess the effect of supplementation with sugar beet silage, corn silage, or high-moisture corn on dairy performance, rumen, and plasma metabolites in dairy cows under conditions of restricted grazing in spring. Eighteen multiparous Holstein Friesian cows, stratified for milk yield (39.4 kg/day ± 3.00), days of lactation (67.0 days ± 22.5), live weight (584 kg ± 38.0), and number of calves (5.0 ± 1.5), were allocated in a replicated 3 × 3 Latin square design. Treatments were as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…In this research, the TVFA concentration ranged from 97.70 to 120.09 mmol/L, consistent with the findings reported by Holmes et al [41]; this is probably because of the good balance between nitrogen and energy of the diet. [42]. This study indicated that feeding HMEC resulted in increased concentrations of ruminal acetic acid as well as TVFA, consistent with the discoveries reported by Allen et al [43].…”
Section: Discussionsupporting
confidence: 91%
“…In this research, the TVFA concentration ranged from 97.70 to 120.09 mmol/L, consistent with the findings reported by Holmes et al [41]; this is probably because of the good balance between nitrogen and energy of the diet. [42]. This study indicated that feeding HMEC resulted in increased concentrations of ruminal acetic acid as well as TVFA, consistent with the discoveries reported by Allen et al [43].…”
Section: Discussionsupporting
confidence: 91%
“…GLU regulates the animal’s vital activities through oxidative energy release or conversion [ 20 ]. Aleixo et al [ 21 ] fed cows with HMC and sugar beet silage separately and found no significant difference in ALB and GLU levels in the serum of cows in the HMC feeding group, indicating that HMC did not have any adverse effects on the cows. In the present study, feeding HMEC had no significant effect on serum levels of AST, ALT, ALB, and GLU in dairy cows, which is similar to the results of the previous study.…”
Section: Discussionmentioning
confidence: 99%